Extração e purificação de corantes obtidos da semente de urucum (Bixa orellana L.) - Miguel, Karolyna Barros (2022)
Currently, consumer demand for natural products has grown on the world stage. There is a growing need in the food industry to replace synthetic dyes with natural ones. Annatto is a fruit of the annatto tree, scientifically known as Bixa orellana L., which is rich in carotenoids. Industrially, it is used in pharmaceutical and cosmetic formulations with great antioxidant capacity and in foods as a natural coloring substitute for chemical additives. The main carotenoid, bixin, is found in the external portion of its seeds. Many organic solvents (ethanol, chloroform, methanol, acetone) have been used in the extraction of carotenoids from annatto seeds and this work explores the exclusive extraction with water, which presented a viable alternative for the extraction and purification process of bixin. Water is not the best solvent for bixin extraction and has little approach in studies proposed in the literature using it as a solvent, but it becomes a viable alternative due to its low cost, lower environmental impact, greater availability and safety in operation. The great diversity of techniques for extracting bixin from annatto seeds ends up producing an extract with impurities such as sugars and proteins. The market increasingly demands from industries a product with a high degree of purity so that there is no risk of contamination in addition to taking advantage of its medicinal properties. The improvement of the characteristics of annatto seed extract can be carried out by the purification process using membranes that allow the concentration and purification of the extract and its bioactives such as phenolics and antioxidant activity. The main objectives of this work were to extract the bixin carotenoid present in annatto seeds through the extraction of chloroform, ethanol and ethanol:water (50:50) (v:v) and water, with subsequent purification by the membrane filtration process, evaluating Bixin content, phenolic compounds and antioxidant activity were determined. Water was not the best solvent for extraction, but for ultrafiltration it became important in the present work because it is less aggressive and preserves the membrane material under study. Bixin extraction was performed at 50°C at a concentration of 1:30 (seed mass: solvent volume) for 60 min, but for chloroform, a time of 240 min was used until complete exhaustion of the seed pigments for quantification. of the total content of bixin present in the seeds. The extract using chloroform showed 10.34% of bixin. The extract using ethanol as solvent showed 8.69 ± 0.04% of bixin, 5.91 ± 0.51 mg EAG/ g of seed for phenolic content, 266.42 ± 4.19 µM trolox/ L of extract for antioxidant activity by the FRAP method and 137.91 ± 12.01 µM trolox/L of extract for antioxidant activity by the ABTS method. For ethanol: water (50:50) (v:v) as solvent showed 7.45 ± 0.01% of bixin, 2.908 ± 0.007 mg EAG/g of seed of phenolic compounds, 129.58 ± 0.70 µM trolox / L of extract for FRAP antioxidant activity and 117.06 ± 1.40 µM trolox/ L of extract for antioxidant activity by the ABTS method. The extract with water as solvent showed 6.02 ± 0.02% of bixin, 2.022 ± 0.003 mg EAG/ g of phenolic compounds seed, 111.3 ± 0.17 µM trolox/ L extract of antioxidant activity by the FRAP method and 96.07 ± 0.35 µM trolox/L extract of antioxidant activity by the ABTS method. The annatto aqueous extract was filtered using a commercial membrane of 10 kDa and a pressure of 6 bar, in order to concentrate the aqueous extract. For comparative purposes, the ethanol extract was filtered (ethanol: water (50:50) (v:v)) under the same conditions as the aqueous extract. The concentrated aqueous extract showed values of 2.18 ± 0.6% for bixin content, 2.53 ± 0.07 mg EAG/ g of seed for phenolic compounds content, 143.80 ± 0.18 µM trolox/ L extract for antioxidant activity (FRAP) and 153.07 ± 2.82 µM trolox/ L extract for antioxidant activity (ABTS). The polymeric membrane was able to concentrate the bixin content by 19.0% in the aqueous extract. For comparative purposes, the same filtration was carried out for the ethanolic extract under the same conditions, using a commercial membrane of 10 kDa and a pressure of 6 bar. The concentrated extract showed values of 0.47 ± 0.04% for bixin content, 2.860 ± 0.07 mg EAG/g seed for phenolic compounds, 112.13 ± 1.17 µM Trolox/L extract for antioxidant activity by the method FRAP and 80.61 ± 0.35 µM Trolox/L extract for antioxidant activity by the ABTS method. These results indicate that the ultrafiltration of the ethanolic extract was not able to concentrate the compounds, as there was an adsorption of the bioactive compounds by the membrane. Thus, the membrane filtration process was efficient for the concentration of bixin present in the aqueous extract.